2004
DOI: 10.1055/s-2004-823779
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Multicenter Masked Comparison Trial of Poractant Alfa (Curosurf) versus Beractant (Survanta) in the Treatment of Respiratory Distress Syndrome in Preterm Infants

Abstract: We compared the onset of clinical response and safety of two surfactants, poractant alfa (Curosurf, Chiesi Pharmaceuticals, Parma, Italy) and beractant (Survanta, Ross Laboratories, Columbus, OH), for treatment of respiratory distress syndrome (RDS) in preterm infants weighing 750 to 1750 g at birth and <35 weeks gestation. The study was performed as a 20-center prospective, randomized, masked comparison trial. Preterm infants (n = 293) with RDS were randomized to receive an initial dose of either 100 (n = 96)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
158
3
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 21 publications
7
158
3
9
Order By: Relevance
“…Ramanathan et al 25 compared poractant alfa with beractant in a multicenter, randomized, controlled trial in the United States. Treatment with poractant alfa was associated with faster weaning of oxygen, fewer additional doses, and decreased mortality in preterm infants <32 weeks gestation when compared with beractant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ramanathan et al 25 compared poractant alfa with beractant in a multicenter, randomized, controlled trial in the United States. Treatment with poractant alfa was associated with faster weaning of oxygen, fewer additional doses, and decreased mortality in preterm infants <32 weeks gestation when compared with beractant.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, 36% of infants randomized to poractant alfa received two or more doses vs 68% in the beractant treated group (P<0.05). In a meta-analysis of the two studies 23,25 comparing beractant vs poractant alfa, neonatal mortality was significantly lower with poractant alfa (odds ratio 0.35, 95% CI 0.13, 0.92). In a recent study comparing these two surfactants, Malloy et al 26 extended the observations of Ramanathan et al 25 They showed improvement in oxygenation to persist up to 48 h ( Figure 1) 26 after treatment with poractant alfa, and a significantly lower number of additional doses with poractant alfa compared to beractant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these factors affect the FiO 2 , oxygenation and the ventilatory requirement especially in the first 24 hours of initial treatment [4,5]. Moreover, text mentions that the lower tidal volumes were targeted in synchronized intermittent mandatory ventilation (SIMV) group but its exact range in mL/kg is missing.…”
Section: High Frequency Oscillatory Ventilation Versus Synchronized Imentioning
confidence: 99%